Explicit finite element methods for equestrian applications - Brolin, K.; Wass, J. (Procedia Engineering, 2016)
A virtual human body model (HBM), developed for vehicle crash simulations, was used to conduct a pilot study of dangerous accidents that occur in equestrian sports. It was performed to illustrate the potential that the explicit finite element (FE) HBMs have to improve rider safety and to assess the protective capacity of the safety vest. Four different questions were addressed: 1 When a rider is trampled by a horse, how does the risk of injury vary with chest impact location? 2 Does a safety-vest provide protection if the rider is kicked by a horse and does the protection vary with the violence of the hoof impact? 3 Can a safety-vest provide any benefit when the rider is hit by the horse after a rotational fall? 4 How does the risk for thoracic injuries vary when the rider falls off the back of a horse at different angles?